A study on the effect of Confucian culture on the work enthusiasm of enterprise employees - XU, Mei (Institutional Knowledge at Singapore Management University, 2023)
Confucianism represents the core of Chinese philosophical ideologies and values, often regarded as the “root” and “source” of Chinese culture. Its influence extends beyond the realm of culture, imparting enduring impacts on the ethical and behavioral norms of Chinese individuals and organizations (Ip, 2009). Xue and Liu (2009) remarked, “It may seem as though the shadow of traditional Confucian culture has faded from view, but regardless of whether one acknowledges it or not, it remains deeply ingrained in the heart of every Chinese individual, serving as the foundation of the Chinese nation.” As a rising economic power, China’s market mechanisms and institutional environments are currently undergoing continuous improvement.